Plan de negocios para la apertura de una sucursal internacional de “Hasta la vuelta Señor” en Nueva York – Estados Unidos - Bedoya Castillo, Camila (2019)
The business plan presented has the objective to check the viability of opening an international branch of the Ecuadorian restaurant “Hasta la vuelta Señor” in New York City – United States. The purpose of opening a business of his type is to position the Ecuadorian food on the American market by a brand that is already recognized in the national market. As part of the viability study, the business environment is analyzed in order to find opportunities and threats. Also, the potential customer is analyzed on the target market to understand their consumption behavior by surveys and interviews to detect their preferences. Then, based on the compiled information, the generic marketing strategy was presented, so as the marketing mix. Finally, the financial evaluation was realized by proforma financial statements projected to five years. Within the evaluation, a financial viability is confirmed by the NPV of $56.198,65 and an IRR of 22,26%.